Asymmetries in Earnings, Employment and Wage Risk in Great Britain - Konstantinos Angelopoulos; Spyridon Lazarakis; Jim Malley (Center for Economic Studies and ifo Institute (CESifo), 2017)
This paper examines the relationship between idiosyncratic risk in labour income and fluctuations in aggregate labour market quantities for Great Britain. We use data from the British Household Panel Survey (BHPS) for 1991-2008 and from the BHPS sub-sample of Understanding Society for 2010-2014. We measure idiosyncratic risk in labour income by the relevant moments of the distributions of earnings, employment and wage shocks across individuals. Our main finding is that idiosyncratic risk increases during contractions in the labour market. Furthermore, we find evidence of insurance, both at the household level and in the form of public insurance. However, private and public insurance mechanisms against an increase in idiosyncratic risk are less eective for households whose head does not hold a University degree.
Keywords: D31; E24; J31; 330; idiosyncratic income risk; employment; social insurance policy